2017
DOI: 10.2527/tas2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

Review: Effects of Ractopamine Hydrochloride (Paylean) on welfare indicators for market weight pigs1

Abstract: This review summarizes the effects of ractopamine hydrochloride (RAC) dose (5, 7.5, 10, and 20 mg/kg) on market weight pig welfare indicators. Ractopamine hydrochloride (trade name Paylean) is a β-adrenergic agonist that was initially approved in the U.S. in 1999 at doses of 5 to 20 mg/kg to improve feed efficiency and carcass leanness. However, anecdotal reports suggested that RAC increased the rate of non-ambulatory (fatigued and injured) pigs at U.S. packing plants. This led to the addition of a caution sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Ractopamine and zilpaterol are feed additives that are used to increase the amount of muscle [27]. High doses of ractopamine were associated with greater difficulty in handling pigs [28,29]. Hot weather is also more likely to increase death losses in cattle fed ractopamine [30,31].…”
Section: Excessive Use Of Growth Promotants and Handling Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ractopamine and zilpaterol are feed additives that are used to increase the amount of muscle [27]. High doses of ractopamine were associated with greater difficulty in handling pigs [28,29]. Hot weather is also more likely to increase death losses in cattle fed ractopamine [30,31].…”
Section: Excessive Use Of Growth Promotants and Handling Problemsmentioning
confidence: 99%
“…Hot weather is also more likely to increase death losses in cattle fed ractopamine [30,31]. Handling problems observed by both the author and reports in the scientific literature both indicate that high doses, combined with hot weather over 32 • C, caused the most problems [8,29]. Pigs fed beta-agonists must be handled in a low-stress manner to prevent downed non-ambulatory animals [32].…”
Section: Excessive Use Of Growth Promotants and Handling Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of ractopamine generates discussion about the countereffects on pigs as the animals tend to be more susceptible to stress due to the effect on heart rate and catecholamine [ 5 ]. In a review carried out by Ritter et al [ 6 ], the authors concluded that the product makes it difficult to handle pigs as it increases their aggressive behavior. Conversely, studies indicate that ractopamine has no impact on the general welfare status of the animals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated advantages for pig production by adding RAC to animal feed such as increased weight gain and improved feed efficiency, increased loin-eye area, meat percentage, meat: fat ratio and reduced back fat thickness (Mimbs et al 2005;Rikard-Bell et al 2009;Athayde et al 2012;Ho et al 2014;Ritter et al 2017;Dalla Costa et al 2018). This improvement in carcass yield is directly related to meat quality, which will result in a higher financial profit to the slaughterhouse.…”
Section: Introductionmentioning
confidence: 99%